Impact of COVID-19 on graduating U.S. pharmacy students in the early epicenter of the pandemic in New York City - Rim Elbeshbeshy (Elsevier, 2021)
Objective: To describe the self-reported impact of the COVID-19 pandemic among final year student pharmacists enrolled in a Doctor of Pharmacy program in New York City during the first peak of the outbreak March through May 2020. Methods: A required senior seminar course for graduating student pharmacists served as a conduit for faculty led monitoring of the wellbeing of the cohort through three data sources: 1) polling data regarding stress factors during a COVID-19 informational session (March 2020), 2) survey data from a 12-item COVID-19 Impact Survey developed and administered electronically in May 2020 and 3) qualitative data from reflection papers mentioning COVID-19. Descriptive statistics, bivariate analysis and thematic analysis were used to summarize data. Results: In March, almost half of respondents (total = 185) reported high personal (47.6%) and school related stress (42.1%). Most students were participating in advanced pharmacy practice experiences (80%) and working in a pharmacy (80%). Survey data (n = 96) revealed the majority of participants perceived negative impact on their future career (69%) and reported concern for people close to them with suspected and confirmed COVID-19. One-third of participants reported knowing someone who died from COVID-19 and 8% were self-confirmed COVID-19 positive. Themes emerging from the reflection papers included: changed perspective, gained experience as a pharmacist during a pandemic, concern for loved ones, and positive outlook. Conclusion: The COVID-19 pandemic had a significant impact on the wellbeing of a cohort of graduating student pharmacists in New York during the initial peaks of the spread in the United States. The results reinforce a need for student support during emergency situations, especially during the final year.